2010
DOI: 10.2478/s11532-009-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pressurised fluid and ultrasonic extraction methods for analysis of plant antioxidants and their antioxidant capacity

Abstract: Abstract:The analytical method based on the high-per formance liquid chromatography coupled with UV detection (HPLC/ UV) for determination of selected antioxidants (i.e., esculetin, scopoletin, 7-hydroxycoumarine, r utin, xanthotoxin, 5-methoxypsoralen and quercetin) in plant material was developed. Pressurised fluid extraction (PFE) and ultrasonic extraction (USE) methods for the isolation of these compounds from ten real plant samples were used. Both extraction methods were optimised and compared to each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…No information have been collected so far regarding this aspect although studies performed on ultrasound assisted extraction from plant wastes showed that phenolic compounds were less degraded (Dobiáš et al, 2010) while carotenoids were strongly affected by the process conditions usually applied (Zhao et al, 2006).…”
Section: Ultrasoundsmentioning
confidence: 98%
“…No information have been collected so far regarding this aspect although studies performed on ultrasound assisted extraction from plant wastes showed that phenolic compounds were less degraded (Dobiáš et al, 2010) while carotenoids were strongly affected by the process conditions usually applied (Zhao et al, 2006).…”
Section: Ultrasoundsmentioning
confidence: 98%
“…Extraction is one of the most important steps in sample pretreatment. Generally, it is a separation process where the distribution of the analyte (in this case, a phenolic compound) between two immiscible phases is made in order to arrive at the appropriate distribution coefficient (Dobiáš et al 2010). The extraction procedure is sequential and systematically carried out using an aqueous organic solvent to extract phenolic compounds in fruit and vegetable samples.…”
Section: Resultsmentioning
confidence: 99%
“…The technique also offers the possibility of working under an inert atmosphere and with protection from light [7]. Although variable results have been obtained, in general, PLE provides similar or better extraction efficiencies than Soxhlet extraction, UAE or MAE, with the additional advantages of requiring smaller amounts of solvent and yielding cleanest extracts [30,31]. PLE has been successfully used for the extraction of flavonoids from grape seeds and skins winemaking wastes [32,33], apples and apple pomaces [34,35] and vegetables [30,36].…”
Section: Extractionmentioning
confidence: 99%